2013
DOI: 10.1002/ca.22218
|View full text |Cite
|
Sign up to set email alerts
|

The value of Tuffier's line for neonatal neuraxial procedures

Abstract: The spine of L4 usually lies on a line drawn between the highest points of the iliac crests (Tuffier's line) in adults. Although its accuracy has been questioned, it is still commonly used to identify the spinous process of the 4 th lumbar vertebra before performing lumbar neuraxial procedures. In children, this line is said to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…In our study, Tuffier's line ranged from the middle thirds of L1 to the middle thirds of S1, with an average level of the middle thirds of L5, which is consistent with a previous report that the median crest height was L5 in children . Another study reported that in neonatal cadavers, the mean level of Tuffier's line was L4/L5 in a prone position . A study involving adults found that the mean level of Tuffier's line was L4/L5 but ranged from L3/L4 to L5/S1 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, Tuffier's line ranged from the middle thirds of L1 to the middle thirds of S1, with an average level of the middle thirds of L5, which is consistent with a previous report that the median crest height was L5 in children . Another study reported that in neonatal cadavers, the mean level of Tuffier's line was L4/L5 in a prone position . A study involving adults found that the mean level of Tuffier's line was L4/L5 but ranged from L3/L4 to L5/S1 .…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, more data are needed to confirm the anatomic relationship in this population. Second, we did not consider changes in position such as lumbar flexion during a spinal block . Most neuroaxial procedure are performed with flexion of the spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the clinicians marked the ICL at the L5 vertebral body as suggested by a recent study of neonatal cadavers in the flexed position 7. The subsequent identification of the LP entry point was not reliable.…”
Section: Discussionmentioning
confidence: 95%
“…In the paediatric and neonatal population, it has been reported to cross the midline at a level between L5 and S1, but this remains an area of debate 6 7…”
Section: Introductionmentioning
confidence: 99%